Answer:
x = -5/9
Step-by-step explanation:
9x + 5 = 0
x = -5/9
if this is incorrect then ur question is missing something
I think it’s the triangle
Subtracting 1 from the function notation will decrease the y-values on the graph by 1 unit.
This will shift then entire graph of f down by 1 unit to create the graph of g.
Use the FOIL method
First, Outside, Inside, Last
(2x -5)(x + 3)
2x(x) = 2x²
2x(3) = 6x
-5(x) = -5x
-5(3) = -15
2x² + 6x - 5x - 15
simplify
2x² + 6x - 5x - 15
2x² + x - 15
2x² + x - 15 is your answer
hope this helps